α-Defensins Promote Bacteroides Colonization on Mucosal Reservoir to Prevent Antibiotic-Induced Dysbiosis - Ou, Jiayao; Liang, Shaonan; Guo, Xue-Kun; Hu, Xiaoyu (Frontiers in Immunology, 2020)
In addition to their established functions in host defense, accumulating evidence has suggested an emerging role for antimicrobial proteins (AMPs) in shaping commensal microbiota. However, the role of α-defensins, the most abundant AMPs of intestine, in regulating microbial ecology remains inconclusive. Here, we report that α-defensins promote commensal Bacteroides colonization by enhancing bacterial adhesion to the mucosal reservoir. Experiments utilizing mice deficient in matrix metalloproteinase 7 (MMP7), the α-defensin–activating enzyme, with rigorous littermate controls showed that α-defensin deficiency did not significantly influence steady-state intestinal microbiota. In contrast, α-defensins are essential for replenishment of commensal Bacteroides from the mucosal reservoir following antibiotics-induced dysbiosis, shown by markedly compromised recovery of Bacteroides in Mmp7−/− animals. Mechanistically, α-defensins promote Bacteroides colonization on epithelial surfaces in vivo and adhesion to epithelial cells in vitro. Moreover, α-defensins unexpectedly does not show any microbicidal activities against Bacteroides. Together, we propose that α-defensins promote commensal bacterial colonization and recovery to maintain microbial diversity upon environmental challenges.